ISOLASI DAN IDENTIFIKASI BAKTERI TANAH YANG TERDAPAT DI SEKITAR PERAKARAN TANAMAN - Sari, Dwi Ratna (BIO-SITE |BIOLOGI Sains Terapan, 2015)
The soil is one habitat of various bacteria. Rhizosphere microbes in the soil near the roots can be beneficial to the plants by forming nodules in some plants Leguminoceae. The bacteria are very helpful in chemical changes in the soil so that the chemicals can be absorbed by plants. The purpose of this research was to determine the type of bacteria that has been found in the soil near and away from plant roots. Bacteria was isolated from soil near and away from the roots at the level 10-5, 10-6, and 10-7 of dilution, each inoculated in duplicate on media Nutient Agar (NA) and incubated for 2x24 hours. Grown colonies and colonies that had thin, beige or transparent, size medium (3mm), and Gram negative characters were sub-cultured. Selected cultures were suspended in concentration about 108 cells / mL 30-50 mL. The identification used the API 20NE. One strip API 20NE. Identification results indicated a positive color change in the media. The research obtained bacteria that has been found near plant roots was Pseudomonas luteola, whereas the bacteria that has been found in away plant roots soil was P. aureuginosa. Â Keyword: soil bacteria, plant roots